Vaginal Vibrator as an alternative to Dilator in vaginal stenosis post pelvic radiotherapy in cervical cancer - Shah, Manjari; Tiwari, Disha (Asian Journal of Medical Sciences, 2021)
Sexuality, post cancer treatment is the most unattended aspect of patient doctor communication. Quality of life in a cancer survivor should be addressed without any inhibitions so that patient does not suffer from any kind of psychological distress. Vaginal stenosis is a well-known side effect of pelvic radiotherapy, which we have tried to address in our study. We have used vaginal vibrator as an alternative to vaginal dilator in two of our patients on experimental basis post vaginal dilator. Both the patients gave feedback that vibrator is comparatively easy to use and less painful. On follow up examination visits, their per vaginal examinations were easy to perform and visibly improved vaginal mucosal health. Psychosexual adjustment is an important domain for better quality of life. Vaginal vibrator is an unorthodox method which we have explored and found some promising results, in overcoming vaginal stenosis and adhesions post pelvic radiation. However, this aspect of treatment as well as method needs to explored.